Past and Future Bank-IFC Cooperation at the Country Strategy Level - Independent Evaluation Group (World Bank, Washington, DC, 2015)
The needs of World Bank Group (WBG) clients have been changing with the private sector increasingly becoming the engine of growth, and the governments attention shifting from public projects to dealing with the growing private sector: regulating it, establishing partnerships with, and/or transferring certain economic activities to it. In this new landscape, the best way to optimize the WBG s development impact, promote its overarching goal of eliminating extreme poverty and boosting shared prosperity in a sustainable manner is to put the array of private sector instruments into full use, bringing enhanced cooperation between the World Bank/International Development Association (the Bank) and IFC at the country level to the forefront. The evidence from the recent past shows that a realistic and selective approach to Bank-IFC cooperation, based on appropriate resource allocation and staff incentives, may yield significantly better outcomes. Thus the challenges of the new Country Program Framework (CPF) process are to: (i) identify where and when cooperation is likely to improve efficiency and development outcome; (ii) redefine job descriptions of various administrative units and re-assign existing staff resources; and (iii) provide staff incentives for joint work.